2008
DOI: 10.1007/s11801-008-7165-9
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis on heat transfer of laser diode module by equivalent electrical network method

Abstract: Because it is complex and inconvenient to use the common temperature field calculating method and experiment method, for analyzing heat transfer properties of laser diode module (LDM), an equivalent electrical network method is presented in this paper. Simulation results show that the temperature stability is closely related to ambient temperature, heat sink, LDM current and TEC current. Ambient temperature and TEC controller are the dominant terms effecting on temperature control in practice.Currently high-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Mitrani [19] proposed a one-dimensional distributed parameter transient model for thermoelectric devices implemented by analogies between the thermal and electrical domains, where thermal variables are described by the corresponding electrical analogues. Through an equivalent electrical network, Yang et al [20] analyzed the temperature control of the LDM by TEC, and demonstrated the steady state of the device.…”
Section: Model Of Ldmmentioning
confidence: 99%
“…Mitrani [19] proposed a one-dimensional distributed parameter transient model for thermoelectric devices implemented by analogies between the thermal and electrical domains, where thermal variables are described by the corresponding electrical analogues. Through an equivalent electrical network, Yang et al [20] analyzed the temperature control of the LDM by TEC, and demonstrated the steady state of the device.…”
Section: Model Of Ldmmentioning
confidence: 99%